Area Bonanza 3

Calculus Level 4

Let x < 1 |x| < 1 .

If f ( x ) = n = 1 n 4 x n f(x) = \sum_{n = 1}^{\infty} n^4 x^n and g ( x ) = n = 1 n 3 x n g(x) = \sum_{n = 1}^{\infty} n^3 x^n , find the area of the region bounded by f f and g g on [ 7 + 33 2 , 0 ] [\dfrac{-7 + \sqrt{33}}{2},0] .


The answer is 0.03635094.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 8, 2018

Let x < 1 |x| < 1 .

n = 1 n x n = j = 1 n = j x n = 1 1 x j = 1 x j = 1 1 x ( x ) 1 1 x = x ( 1 x ) 2 \sum_{n = 1}^{\infty} n x^n = \sum_{j = 1}^{\infty} \sum_{n = j}^{\infty} x^n = \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} x^{j} = \dfrac{1}{1 - x}(x)\dfrac{1}{1 - x} = \dfrac{x}{(1 - x)^2}

( x x 1 ) ( 1 x ) ( x x 1 ) = x ( x 1 ) 2 . (\dfrac{x}{x - 1})(\dfrac{1}{x})(\dfrac{x}{x - 1}) = \dfrac{x}{(x - 1)^2}.

n = 1 n 2 x n = j = 1 ( n = j n x n ) = \sum_{n = 1}^{\infty} n^2 x^n = \sum_{j = 1}^{\infty} (\sum_{n = j}^{\infty} n x^n) = 1 1 x j = 1 ( j x j ) + x ( 1 x ) 2 j = 1 x j = \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} (j x^j) + \dfrac{x}{(1 - x)^2}\sum_{j = 1}^{\infty} x^j =

( 1 1 x ) ( x ( 1 x ) 2 ) + ( x ( 1 x ) 2 ) ( x 1 x ) = (\dfrac{1}{1 - x})(\dfrac{x}{(1 - x)^2}) + (\dfrac{x}{(1 - x)^2})(\dfrac{x}{1 - x}) = x 2 + x ( 1 x ) 3 \dfrac{x^2 + x}{(1 - x)^3} .

g ( x ) = n = 1 n 3 x n = j = 1 n = j n 2 x n = g(x) = \sum_{n = 1}^{\infty} n^3 x^n = \sum_{j = 1}^{\infty} \sum_{n = j}^{\infty} n^2 x^{n} = 1 1 x j = 1 j 2 x j + 2 x ( 1 x ) 2 j = 1 j x j + x 2 + x ( 1 x ) 3 j = 1 x j = ( 1 1 x ) ( x 2 + x ( 1 x ) 3 ) + \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} j^2 x^j + \dfrac{2x}{(1 - x)^2}\sum_{j = 1}^{\infty} j x^j + \dfrac{x^2 + x}{(1 - x)^3}\sum_{j = 1}^{\infty} x^j = (\dfrac{1}{1 - x})(\dfrac{x^2 + x}{(1 - x)^3}) + ( 2 x ( 1 x ) 2 ) ( x ( 1 x ) 2 ) + ( x 2 + x ( 1 x ) 3 ) ( x 1 x ) = (\dfrac{2x}{(1 - x)^2})(\dfrac{x}{(1 - x)^2}) + (\dfrac{x^2 + x}{(1 - x)^3})(\dfrac{x}{1 - x}) = x 3 + 4 x 2 + x ( 1 x ) 4 \dfrac{x^3 + 4x^2 + x}{(1 - x)^4} .

f ( x ) = n = 1 n 4 x n = j = 1 n = j n 3 x n = f(x) = \sum_{n = 1}^{\infty} n^4 x^n = \sum_{j = 1}^{\infty} \sum_{n = j}^{\infty} n^3 x^{n} = 1 1 x j = 1 j 3 x j + 3 x ( 1 x ) 2 j = 1 j 2 x j + 3 ( x 2 + x ) ( 1 x ) 3 j = 1 j x j + x 3 + 4 x 2 + x ( 1 x ) 4 j = 1 x j = \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} j^3 x^j + \dfrac{3x}{(1 - x)^2}\sum_{j = 1}^{\infty} j^2 x^j + \dfrac{3(x^2 + x)}{(1 - x)^3}\sum_{j = 1}^{\infty} j x^j + \dfrac{x^3 + 4x^2 + x}{(1 - x)^4}\sum_{j = 1}^{\infty} x^j =

= ( 1 1 x ) ( x 3 + 4 x 2 + x ( 1 x ) 4 ) + = (\dfrac{1}{1 - x})( \dfrac{x^3 + 4x^2 + x}{(1 - x)^4}) + ( 3 x ( 1 x ) 2 ) ( x 2 + x ( 1 x ) 3 ) + ( 3 ( x 2 + x ) ( 1 x ) 3 ) ( x ( 1 x ) 2 ) + (\dfrac{3x}{(1 - x)^2})(\dfrac{x^2 + x}{(1 - x)^3}) + (\dfrac{3(x^2 + x)}{(1 - x)^3})(\dfrac{x}{(1 - x)^2}) + x 3 + 4 x 2 + x ( 1 x ) 4 ( x 1 x ) = x 4 + 11 x 3 + 11 x 2 + x ( 1 x ) 5 \dfrac{x^3 + 4x^2 + x}{(1 - x)^4}(\dfrac{x}{1 - x}) = \dfrac{x^4 + 11x^3 + 11x^2 + x}{(1 - x)^5} .

Let u = 1 x d u = d x 7 + 33 2 0 g ( x ) d x = 1 9 33 2 u 3 7 u 2 + 12 u 6 u 4 d u = u = 1 -x \implies du = -dx \implies \int_{\frac{-7 + \sqrt{33}}{2}}^{0} g(x) dx = -\int_{1}^{\frac{9 - \sqrt{33}}{2}} \dfrac{u^3 - 7u^2 + 12u - 6}{u^4} du = 1 9 33 2 1 u 7 u 2 + 12 u 3 6 u 4 d u = -\int_{1}^{\frac{9 - \sqrt{33}}{2}} \dfrac{1}{u} - 7u^{-2} + 12u^{-3} - 6u^{-4} du = ( ln ( u ) + 7 u 6 u 2 + 2 u 3 ) 1 9 33 2 = -(\ln(u) + \dfrac{7}{u} - \dfrac{6}{u^2} + \dfrac{2}{u^3})|_{1}^{\frac{9 - \sqrt{33}}{2}} = ( ln ( 33 9 2 ) + 83 33 765 576 ) = -(\ln(\dfrac{\sqrt{33} - 9}{2}) + \dfrac{83\sqrt{33} - 765}{576}) = 765 83 33 576 ln ( 9 33 2 ) 0.01317003 \dfrac{765 - 83\sqrt{33}}{576} - \ln(\dfrac{9 - \sqrt{33}}{2}) \approx \boxed{0.01317003}

and,

7 + 33 2 0 f ( x ) d x = 1 9 33 2 u 4 15 u 3 + 50 u 2 60 u + 24 u 5 d u = 1 9 33 2 1 u 15 u 2 + 50 u 3 60 u 4 + 24 u 5 d u = \int_{\frac{-7 + \sqrt{33}}{2}}^{0} f(x) dx = \int_{1}^{\frac{9 - \sqrt{33}}{2}} \dfrac{u^4 - 15u^3 + 50u^2 - 60u + 24}{u^5} du = \int_{1}^{\frac{9 - \sqrt{33}}{2}} \dfrac{1}{u} - 15u^{-2} + 50u^{-3} - 60u^{-4} + 24u^{-5} du = ( ln ( u ) + 15 u 25 u 2 + 20 u 3 6 u 4 ) 1 9 33 2 = (\ln(u) + \dfrac{15}{u} - \dfrac{25}{u^2} + \dfrac{20}{u^3} - \dfrac{6}{u^4})|_{1}^{\frac{9 - \sqrt{33}}{2}} = ln ( 9 33 2 ) + 6087776403456 + 396474974208 33 2348273369088 4 \ln(\dfrac{9 - \sqrt{33}}{2}) + \dfrac{6087776403456 + 396474974208\sqrt{33}}{2348273369088} - 4 0.04952097 \approx \boxed{0.04952097}

7 + 33 2 0 f ( x ) g ( x ) d x = 0.03635094 \implies \int_{\frac{-7 + \sqrt{33}}{2}}^{0} f(x) - g(x) dx = \boxed{0.03635094}

Your problems tend to be extremely computational, sir. Perhaps making the computation less heavy would make the problems more approachable (I like the idea behind your problems but once I see the computaiton, i get discouraged) Thanks.

D S - 3 years ago

Log in to reply

Thank you. Your right, at times I get carried away. In the future I'll attempt to make my problems less computational.

Rocco Dalto - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...